STRATEGI HUMAS DIGITAL BADAN NARKOTIKA NASIONAL PROVINSI JAWA TIMUR DALAM MEMBUAT KONTEN PENCEGAHAN PENYALAHGUNAAN NARKOBA (Studi Media Sosial Instagram @infobnnp_jatim dan Website jatim.bnn.go.id) - Cahyani, Rinda Meilda; ., Mutiah (The Commercium, 2024)
The research focuses on Digital Public Relations of the National Narcotics Agency of East Java Province in using public relations strategies related to the delivery of information or messages to the public in the creation of a drug abuse prevention content on the social media account Instagram and the official website owned. This research was carried out to find out what I was doing by the Public Relations of the National Narcotics Agency of East Java Province in adapting the content of information or messages of prevention of drug abuse to the public. The research uses a qualitative approach to the case study methodology through in-depth interviews as the primary method of data collection. The theory used in this study is the theory of public relations strategies. The results of this study show that the Public Relations National Narcotics Agency of Eastern Java Providence uses public relations strategy in the creation of drug abuse prevention content as a medium of information or message to the public.